2017
DOI: 10.1002/jsfa.8191
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Hermetia illucens larvae meal on rainbow trout (Oncorhynchus mykiss) feed: effect on sensory profile according to static and dynamic evaluations

Abstract: Inclusion of Hermetia illucens larvae meal on rainbow trout (Oncorhynchus mykiss) feed: effect on sensory profile according to static and dynamic evaluations / Borgogno, Monica; Dinnella, Caterina; Iaconisi, Valeria; Fusi, Renzo; Scarpaleggia, Claudia; Schiavone, Achille; Monteleone, Erminio; Gasco, Laura; Parisi, Giuliana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 30 publications
5
51
1
Order By: Relevance
“…Borgogno et al . () recently showed that SFAs positively correlated with metallic aroma/flavour, overall flavour and tenderness of boiled rainbow trout ( Oncorhynchus mykiss ) and that MUFAs correlated positively with boiled fish flavour and overall aroma, thus confirming the relations found in the present trial. In addition, sample discrimination according to sensory texture (TxS) had a low RV coefficient with respect to laboratory determined texture (TxI) which means that the two parameters did not discriminate samples in the same way.…”
Section: Resultssupporting
confidence: 90%
“…Borgogno et al . () recently showed that SFAs positively correlated with metallic aroma/flavour, overall flavour and tenderness of boiled rainbow trout ( Oncorhynchus mykiss ) and that MUFAs correlated positively with boiled fish flavour and overall aroma, thus confirming the relations found in the present trial. In addition, sample discrimination according to sensory texture (TxS) had a low RV coefficient with respect to laboratory determined texture (TxI) which means that the two parameters did not discriminate samples in the same way.…”
Section: Resultssupporting
confidence: 90%
“…Recently, authors have found that changes in the dietary protein sources, such as type and quantity, did not affect textural attribute of rainbow trout fillets. Indeed, Borgogno et al (2017) verified that the Warner-Bratzler shear force registered for rainbow trout muscle was unaffected with increasing substitution levels of fishmeal with insect meal, however, the performed sensory analysis revealed that differences between dietary treatments were perceived by trained panellist in terms of fillet textural attributes (tenderness, juiciness, fibrousness). Since no effect of the experimental diet on shear force emerged in the present trial, further studies would be useful to understand if texture might be perceived as different by a trained panel or if liking judgements of fillets by consumers might be altered by the composition of the feed utilised for feeding the fish, as found by Bruni et al (2020).…”
Section: Fish Performances Marketable and Physical Characterisationmentioning
confidence: 81%
“…62 Conflicting results exist regarding the effects of insect meal on sensory attributes of fish fillets in the literature. Insect meal was reported to affect sensory profile of the fillets of Atlantic salmon 60 and rainbow trout, 63 but other studies did not observe any sensory differences in Atlantic salmon, 64 rainbow trout, 58 or common carp. 65 Challenges of incorporating insect meal into aquaculture feeds include the variable and sometimes less ideal nutritional profiles.…”
Section: Insectsmentioning
confidence: 92%